Tasks and role performance of childminders and self-reliance of preschool-aged children - Decano, Ivan Arthur D.C; Sagad, Ira Jean Camille D.
The quality of care received by young children is dependent on various factors. In the Philippines, there is an increase in employment of childminders by parents to provide care for their children. In this study, the tasks and role performance of the childminder were described, enabling the researchers to test the relationship of the childs self-reliance and their childminders role performance. A total of 29 childminders of children studying in U.P. CDC participated in an in-depth interview on their tasks and role performance. The results were organized according to similar themes. The results showed that childminders are assigned tasks such as caring for the child through feeding and bathing, and household chores. The manner by which these tasks are executed also varies owing to various factors such as the childs abilities and mood, and other tasks that are assigned to the childminder. The self-reliance scores of the respective 29 children of the childminders were also collected and tested in contrast to the answers of the childminders. Using Mann-Whitney U test, it was proven that children with childminders who provide more assistance have statistically greater self-reliance scores than those of childminders who provide less. The findings emphasize the importance of the tasks and role performance of childminders on the children they mind and contradict present literature that argue that children become more self-reliant when their caregivers extend only little assistance. Other factors such as length of time the childminder has been in-charge of the child and the type of school the child studies in can also be studied in relation to the childs self-reliance.